A new species of the subfamily Aphodiinae (Coleoptera: Scarabaeidae) from the Lower Cretaceous of Transbaikalia - G.V. Nikolajev (Кавказский энтомологический бюллетень, 2008)
Aphodius (s. lato) cretaceous Nikolajev, sp. n. from the Lower Cretaceous of Transbaikalia (Baissa locality) is described. The genus Cretorabaeus Nikolajev, 1995 is transferred to the subfamily Aphodiinae (tribus incertus).